2012
DOI: 10.1007/s11606-012-2138-x
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in the Effect of a Telephone-Delivered Hypertension Disease Management Program

Abstract: (152), Durham, NC, USA.BACKGROUND: African Americans are significantly more likely than whites to have uncontrolled hypertension, contributing to significant disparities in cardiovascular disease and events. OBJECTIVE: The goal of this study was to examine whether there were differences in change in blood pressure (BP) for African American and non-Hispanic white patients in response to a medication management and tailored nurse-delivered telephone behavioral program. PARTICIPANTS: Five hundred and seventy-thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(82 citation statements)
references
References 34 publications
3
79
0
Order By: Relevance
“…18,19 In a nurse-managed intervention in the VA setting, Jackson, et al reported that the intervention effect was confined to African American patients. 20 Although we did not observe significant interactions by baseline SBP level or race, our results extend these previous reports and provide useful information on subgroups that also suggests likely mechanisms by which our intervention, and perhaps similar interventions designed by others, may exert their beneficial effects.…”
Section: Discussionsupporting
confidence: 84%
“…18,19 In a nurse-managed intervention in the VA setting, Jackson, et al reported that the intervention effect was confined to African American patients. 20 Although we did not observe significant interactions by baseline SBP level or race, our results extend these previous reports and provide useful information on subgroups that also suggests likely mechanisms by which our intervention, and perhaps similar interventions designed by others, may exert their beneficial effects.…”
Section: Discussionsupporting
confidence: 84%
“…30 A similar study in two internal medicine clinics in North Carolina found that a behavioral intervention and home BP monitoring was more effective in non-white patients than whites. 31 A nurse led intervention tailored specifically to blacks and Hispanics in Harlem, NY found a significant reduction in systolic BP in comparison to usual care.…”
Section: Discussionmentioning
confidence: 94%
“…73 The inclusion of technology-based or mobile health (mHealth) interventions 74, 75 should be considered to test whether they can enhance culturally-appropriate community-based programs. This can include telephone-delivered hypertension management programs 76, 77 in conjunction with HBPM, or ABPM and/or mobile phone text messaging to support medication adherence. 78, 79 Smartphone technology can also be used to facilitate data collection, including ecological momentary assessments among JHS participants between study visits and deliver or re-emphasize healthcare education 80 and lifestyle interventions.…”
Section: Treatment and Control Issuesmentioning
confidence: 99%